2006
DOI: 10.1002/gcc.20349
|View full text |Cite
|
Sign up to set email alerts
|

IncreasedWSB1copy number correlates with its over-expression which associates with increased survival in neuroblastoma

Abstract: Gain of chromosome 17 is the most prevalent genetic abnormality identified in neuroblastoma (NB) and distal 17q gain has prognostic significance in NB. In this report, we have combined array-based comparative genomic hybridization (A-CGH) and gene expression analysis to investigate gene copy number changes and its impact on the gene expression level as well as their association with prognosis genes located on chromosome 17 in NB tumors. We observed differential gains of chromosome 17 between Stages 4- and 4S t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
5
25
0
Order By: Relevance
“…Until the gene dosage hypothesis is experimentally proven and the actual causal 17q genes have been identified, other hypotheses, however, also remain valid. One of these hypotheses constitutes an imbalance for genes located on both sides of the breakpoint as originally suggested by Bown et al 3 This hypothesis was also put forward by Chen et al, 33 in the light of the finding of overexpression of the WSB1 gene, located at 17q11, in favorable NB with whole chromosome 17 gain (also confirmed in our recent study by comparing the expression profiles of NB and normal fetal neuroblasts 12 ). Although the 17q gain enigma in NB remains to be resolved, the integrative analysis of genome and transcriptome profiles, as illustrated in our study, is a promising approach to identify candidate dosage sensitive genes.…”
supporting
confidence: 72%
“…Until the gene dosage hypothesis is experimentally proven and the actual causal 17q genes have been identified, other hypotheses, however, also remain valid. One of these hypotheses constitutes an imbalance for genes located on both sides of the breakpoint as originally suggested by Bown et al 3 This hypothesis was also put forward by Chen et al, 33 in the light of the finding of overexpression of the WSB1 gene, located at 17q11, in favorable NB with whole chromosome 17 gain (also confirmed in our recent study by comparing the expression profiles of NB and normal fetal neuroblasts 12 ). Although the 17q gain enigma in NB remains to be resolved, the integrative analysis of genome and transcriptome profiles, as illustrated in our study, is a promising approach to identify candidate dosage sensitive genes.…”
supporting
confidence: 72%
“…A gene expression analysis of 37 neuroblastoma patients revealed that increased WSB1 copy number correlates with good prognosis (28). In contrast, reduced cell proliferation and enhanced resistance to apoptosis are observed in both pancreatic cancer cells and neuroblastoma cells after WSB1 overexpression (16,29).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore reanalysed the expression of four genes which showed significant copy number dependent expression (PMP22, WSB1, BRCA1 and BIRC5) using real-time PCR. These genes were chosen as they map to distinct regions of chromosome 17 (17p12, 17q11, 17q21 and 17q25, respectively), and because they have been implicated previously in neuroblastoma or other cancers (Chen et al, 2006;Deng, 2006;Miller et al, 2006). Significant correlations were observed between Affymetrix and real-time PCR data for all four genes, r 2 varying from 0.683 for BRCA1 to 0.961 for PMP22 (Supplementary Figure 2S).…”
Section: Resultsmentioning
confidence: 99%